2018
DOI: 10.1515/cipms-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Marginal Bone Loss Around Dental Implants and the Specific Characteristics of Implant-Prosthetic Treatment

Abstract: The marginal bone loss around dental implants is an important indicator that helps to evaluate the course and the final outcome of implant-prosthetic treatment. It is, therefore, important to understand the factors that may affect this. The aim of the study was to assess the impact of the specific characteristics of implant-prosthetic treatment on the marginal bone loss around implants. The study included 28 patients, aged 37-66 years, treated with dental implants. Every patient received at least one of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Bridges with six points exhibited the least favorable mechanical properties compared to shorter or longer ones. Bridge restorations generally revealed better marginal bone preservation compared to overdentures, which is also confirmed in the literature [21].…”
Section: Multiple Retention Losses After 5 Yearssupporting
confidence: 79%
See 1 more Smart Citation
“…Bridges with six points exhibited the least favorable mechanical properties compared to shorter or longer ones. Bridge restorations generally revealed better marginal bone preservation compared to overdentures, which is also confirmed in the literature [21].…”
Section: Multiple Retention Losses After 5 Yearssupporting
confidence: 79%
“…Is this standard still valid in this century? Recent studies have shown that marginal bone loss depends on factors such as tobacco smoking, the presence or absence of platform switching, cement remnants, overloading in occlusion, poor oral hygiene, and the type of prosthetic restoration [17][18][19][20][21].…”
Section: Multiple Retention Losses After 5 Yearsmentioning
confidence: 99%
“…The technique of immediate loading was designed because of reduced surgical trauma, improved healing, reduced time of treatment as well as conservation of bone and soft tissues and enhancement of esthetics; these is an agreement with Singh and his colleagues (10) .…”
Section: Discussionmentioning
confidence: 54%
“…Marginal bone loss occurs when bone tissue resorbs near the neck of dental implants. Various factors can influence bone metabolism near the implant neck, such as cigarettes, oxidative stress, smoking, prosthetic restoration, surgical techniques, operator skill, torque during implant insertion, and the general condition (GC) of patients, including calcium phosphate metabolism and bone-healing capacity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%